1998
DOI: 10.1128/jvi.72.4.3401-3406.1998
|View full text |Cite
|
Sign up to set email alerts
|

Molluscum Contagiosum Virus Topoisomerase: Purification, Activities, and Response to Inhibitors

Abstract: Molluscum contagiosum virus (MCV), the only member of theMolluscipoxvirus genus, causes benign papules in healthy people but disfiguring lesions in immunocompromised patients. The sequence of MCV has been completed, revealing that MCV encodes a probable type I topoisomerase enzyme. All poxviruses sequenced to date also encode type I topoisomerases, and in the case of vaccinia virus the topoisomerase has been shown to be essential for replication. Thus, inhibitors of the MCV topoisomerase might be useful as ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 29 publications
1
22
0
Order By: Relevance
“…A network of contacts extending from −1 to the +9 region stabilize the catalytic domain in an active conformation (Perry et al, 2006). This is consistent with biochemical studies, which indicated that the topoisomerase when bound covers a considerably larger site than just the conserved 5′-(T/C)CCTT-3′ (Hwang, Burgin, and Bushman, 1999;Hwang et al, 2006;Hwang, Wang, and Bushman, 1998;Sekiguchi and Shuman, 1994). Comparison of the structure of the catalytic domain in the presence and absence of DNA indicates that DNA contacts stabilize a major conformational change which assembles the active site Perry et al, 2006).…”
Section: Introductionsupporting
confidence: 80%
See 4 more Smart Citations
“…A network of contacts extending from −1 to the +9 region stabilize the catalytic domain in an active conformation (Perry et al, 2006). This is consistent with biochemical studies, which indicated that the topoisomerase when bound covers a considerably larger site than just the conserved 5′-(T/C)CCTT-3′ (Hwang, Burgin, and Bushman, 1999;Hwang et al, 2006;Hwang, Wang, and Bushman, 1998;Sekiguchi and Shuman, 1994). Comparison of the structure of the catalytic domain in the presence and absence of DNA indicates that DNA contacts stabilize a major conformational change which assembles the active site Perry et al, 2006).…”
Section: Introductionsupporting
confidence: 80%
“…Studies of DNA relaxation by poxvirus topoisomerases in vitro have often used the bacterial plasmid pUC19 as a substrate, and in the course of this work the topoisomerase recognition sites have been carefully quantified (Hwang, Wang, and Bushman, 1998;Shuman, 1991;Shuman and Prescott, 1990). To assess whether the PWM determined above is a reliable predictor of favored sites, we used it to predict sites in pUC19, then compared the calls to experimental results.…”
Section: Experimental Validation Of Predicted Topoisomerase Sitesmentioning
confidence: 99%
See 3 more Smart Citations